OWE-34 ADR in CRC screening programs: Master show me the way to become a high detector!. (June 2019) - Rosa-Rizzotto, Erik; Caroli, Diego; Monica, Fabio; Mario, Saia; Zorzi, Manuel; Capodaglio, Giulia; Turrin, Anna; Narne, Elena; Lazzari, Franca De; ,
Abstract : Background: Although the adenoma detection rate (ADR) cut-off for colonoscopies after positive fecal immunochemical tests (FIT) continues to be a debated issue, the ADR is one of the most accepted benchmarks for colonoscopy quality. There is some evidence that the quality of colonscopy screening can be improved by educational interventions. This study aimed to analyze the effect of endoscopist-related characteristics on colonoscopy quality indicators and to evaluate the factors affecting ADR patterns registered in the colorectal (CRC) screening program in the Veneto Region between 201–017. Methods the following data about endoscopists in screening programs between 201–017 were collected: age, sex, years as physician, specialization, annual colonoscopy volume. During 201–014, younger endoscopists (<40 yr) underwent four meetings with a senior endoscopist (Cristopher Williams), to improve general endoscopic ability and, in particular, the sensibility to detect adenomatous lesions. ADR was calculated for each operator. Data were analyzed with SPSS program. Results: During the three year period, 191 endoscopists performed a total of 42, 706 first colonoscopies after FIT positivity. One hundred forty with at least 20 colonoscopies after FIT positivity/yr, (mean age 48.2yr ± 10.8yr (M±SD), Male 53.9%) were selected. Three hundred eight-two ADRs were collected during the observation period. Overall ADR was 43.7±9.5%. Ninety-six of the endoscopists were specialized in gastroenterology, 35 in general surgery, and 8 in other specialities. ADR was 44.1± 9.7% for the gastroenterologists, 42.7 ±9.6% for the surgeons (p=ns) and 39.5 ±7% for those with other specialities (p=0.033). ADR was significantly higher for the younger endoscopists (3–9yr 47.5%; 4–9yr 44.6%; >50yr 41.4%, with p<0.001). The ADRs over the three year period were similar (44.2% vs 42.9% vs 43.3%, p= ns). No significant association between ADR and number of screening colonoscopies performed weew found. When the ADR in 2017 of 81 endoscopists was analyzed depending on the cumulative number of total colonoscopies/yr, it was found that the those with > 300 colonoscopies/yr had higher ADRs ( 35.5 ±21.4% vs 43.5±11.5%, p=0.04) in colonoscopies after FIT positivity/yr . Conclusions: Study findings demonstrated that junior endoscopists and those specialized in gastroenterology were more effective in identifying adenomas during screening colonscopy procedures. High annual colonoscopy volumes and working exclusively as endoscopists but not years of experience or being older were associated with higher ADRs. Educational interventions seemed to be effective in improving sensitivity and performance.